LSP transcoding method between 3GPP AMR-NB and ITU-T G.729A based on GMM - LIU Zhang-yu; BAO Chang-chun; QIU Jian-wei; XU Hao (Tongxin xuebao)
An efficient transcoding algorithm of LSP（line spectrum pairs） parameters based on GMM（Gaussian mixture model） was proposed and implemented through the mathematical analysis of GMM.Meanwhile,several practical issues in details were analyzed under experiments.The experiments indicate that the computational complexity of the proposed LSP transcoding algorithm is reduced by above 78% and the transcoded speech quality is not worse than DTE method.